Bireuen Sports Center - muliani muliani (Jurnal Ilmiah Mahasiswa Arsitektur dan Perencanaan, 2019)
Bireuen sports center is the sports zone embodies sports event for community, particularly in bireuen . Bireuen sports center is supported by the government regulation about with development has worn sports the listed hearts act 3 of 2005 which states that the government, local government and society has a responsibility to review plan sports infrastructure in the each region. Designing Bireuen Sports Center is not only intended as a facility, but it’s can accommodate sports activities for the community and also to provide a container that responds to the environmental footprint , future buildings and circulation patterns both inside and outside the building . Therefore , the design of this sports area using the theme of the high- tech approach in order to realize the buildings are able to adapt to the surrounding environment and using the elements technology. High - Tech theme in the design applied to the selection of materials, structures, construction and design of the building.